2006
DOI: 10.1051/rnd:2005063
|View full text |Cite
|
Sign up to set email alerts
|

A protein-free diet alters small intestinal architecture and digestive enzyme activities in rats

Abstract: -The consequences of feeding a protein-free (PF) diet, as compared to casein, on gut characteristics were studied in slightly energy-restricted rats fed similar amounts of feed for 10 d. The weight and pH of fresh digesta in the stomach were lower (P = 0.045 and P = 0.016). However, the weight of fresh digesta in the other segments and gut tissue weight were not significantly affected by the diet (P > 0.05). Small intestinal crypt depth, width and area were reduced by 13, 23 and 37%, respectively (P = 0.011, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Montoya et al (2006) stated that the specific activity of amino peptidase was reduced at different sites of the small intestine in the rats fed a proteinfree diet, our findings also agreed with those of Montoya. In conclusion, consumption of a protein-deficient diet altered the villous-crypt architecture and enzyme activities in rats.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Montoya et al (2006) stated that the specific activity of amino peptidase was reduced at different sites of the small intestine in the rats fed a proteinfree diet, our findings also agreed with those of Montoya. In conclusion, consumption of a protein-deficient diet altered the villous-crypt architecture and enzyme activities in rats.…”
Section: Resultssupporting
confidence: 92%
“…Malnutrition causes a combination of metabolic changes that lead to weight loss, disorder in growth, damage of jejunal cell mucosa and change in the function of the gastrointestinal tract especially liver and small intestine (Montoya et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Our data show that AKG acid provided at 3 g/kg feed has a negative effect on villi and microvilli length as reported by Montoya et al (2006). On the contrary, the data obtained with AKG acid at 6 g/kg feed are similar to those of the control group.…”
Section: Alpha-ketoglutaric Acid In Growing Ratssupporting
confidence: 86%
“…Many studies suggest that protein malnutrition causes alterations on adult rat ascending colon intestinal morphometrics, especially in tissues which present a high level of cell turnover such as the mucosa tunic and consequently their structures such as the enterocytes, goblet cells, and crypts (Hermes et al, 2008). Montoya et al (2006) showed that feeding a protein free diet to rats slightly restricted in energy affected gastric emptying and small intestinal mucosal architecture and enzyme activities. Compared with malnourished rats in the group phase of refeeding, the levels of total serum protein and albumin were significantly increased.…”
Section: Discussionmentioning
confidence: 99%